The Visual and Refractive Status in One Sample Population of ‘Orang Asli’(Indigenous) Children in Hulu Langat, Selangor - MN, Fairuz; MF, Noor Farasuhana; AI, Mohd Zaki; S, Noorsuhaila (Bangladesh Journal of Medical Science, 2020)
Background: The aim of this study is to assess the visual and refractive status among ‘Orang Asli’ (indigenous) children in Kampung Sungai Lalang, Semenyih, Selangor. Uncorrected refractive error is a major burden among children around the world. It results in a significant number of problems among this high-risk group including educational loss, low productivity and impaired quality of life. Besides that, there are lacking information regarding vision problems among aborigine children or ‘Orang Asli’ in Malaysia. This study was undertaken to determine the prevalence of refractive error, and the association of the refractive error and visual acuity with age among ‘Orang Asli’ children. Methods: A cross sectional study was conducted on ‘Orang Asli’ children (n=43) where 51.2% were male and 48.8% were female. Visual acuity and refraction assessment were done on every child using Refractive Error Study in School Children (RESC) protocol. Results: The prevalence of refractive error was simple myopia (1.2%), simple hyperopia (18.6%), compound myopic astigmatism (7.0%), and mixed astigmatism (73.3%) respectively. The visual acuity measurement shows that the majority of subjects achieved 6/6 represented by 88.4% of the right eye and 86% of the left eye. There is no association between refractive error and age (P>0.05). Conclusion: This study concludes that there is a high prevalence of hyperopia among ‘Orang Asli’ children and There is no association of refractive error with age and gender. Therefore, there is a need to create better awareness programs among the parents about the importance of eye examination to their children. Bangladesh Journal of Medical Science Vol.19(4) 2020 p.609-613